Pacaran dalam Formasio Keluarga Kristiani: Sebuah Refleksi Teologis atas Pacaran sebagai Persiapan Membangun Keluarga Kristiani - Purnomo, Sebastianus Joko (Felicitas, 2021)
Dating is a preparation for building a married life by getting to know and love each other's partners. However, during this courtship period, young people sometimes face challenges in controlling sexual desire, so that many of them have sexual intercourse while dating. Dating is sometimes interpreted as being able to freely have sexual relations. In this case, the courtship is clearly incompatible with Christianmorals, because sexual relations only occur in a legal marriage as an expression of total conjugal love. Therefore, first of all, Catholic Young People need to re-recognize the Christian vocation to holiness which is shaped in acts of love and confirmed by sacramental grace. Thus, they really interpret dating as an initial formation in building a Christian family that also goes towards holiness.